Effect of sand granulometry on the egg hatchling success of the sea turtle Caretta caretta - Tacchi, Maria Fernanda; Peres Quirino, Fernanda; Martins Ferreira, Diego Júnior; Gomes Afonso, Lílian; Tognin, Federico; Negreiros, Daniel (Neotropical biology and conservation, 2019)
The environmental characteristics of nesting sites of sea turtles may directly interfere with the egg hatchling success. The objective of the present study was to evaluate the factors that affect the success of hatchling in the nests of the loggerhead sea turtle ( Caretta caretta ). Data from 37 nests of C. caretta from the coast of Mata de São João, Bahia, northeastern Brazil, were obtained from TAMAR, Sauípe station. Samples of sand were collected in each nest to determine the granulometry. A significant negative relationship was found between the stillborn rate and the fine sand ratio (r 2 = 0.119; p = 0.036), indicating that a larger fraction of fine sand had a positive effect on nest hatchling success. The egg laying date also had a significant influence on the rate of stillbirths (r 2 = 0.163; p = 0.013), with a trend towards a higher stillbirth rate, the later the laying date of the eggs. There is indication that the transfer of eggs to sites with more favorable characteristics may be considered as a potential alternative to increase the hatchling success rate of C. caretta eggs.